Parents' Acceptance of Learning about Mindfulness for Managing Pediatric Asthma - Mala Mathur; Karen Pletta; Bradley R. Kerr; Jens Eickhoff; Robin Puett; Megan A. Moreno (MDPI AG, 2020)
Background: Emerging research suggests mindfulness may reduce stress and asthma symptoms in children, yet there is a gap in understanding parental views towards learning about mindfulness. Objective: This study aimed to compare the perceived acceptance to learn about mindfulness among parents of children with and without asthma, and to understand differences across income levels. Methods: This was a national, cross-sectional, online survey of parents of children 0-18 years. Acceptance was measured with questions on whether parents believe mindfulness could be beneficial while parenting, and if they would be willing to learn about mindfulness. Comparisons of mindfulness acceptance between income level were conducted using chi-square and Fisher's exact test. Results: Parents of children with asthma were more likely to be interested in learning about mindfulness from their health care provider compared to those without asthma (46% vs. 38%, p < 0.0001). At all income levels examined in the study, parents (63-75%) of children with asthma indicated that they agreed or strongly agreed that mindfulness can be beneficial when parenting. Conclusion: Findings suggest an opportunity to incorporate mindfulness teaching into asthma care for pediatric patients of all income levels.